Horseshoe kidney, complex radionuclide examination - Tertychna, Daryna; Romanenko, Anna; Tkachenko, Mikhail (The Ukrainian Scientific Medical Youth Journal, 2022)
The article examines the issue of establishing the functional ability of the horseshoe kidney both in general and in its nominal parts, using dynamic renoscintigraphy. Such studies are necessary for children of any age with detected anomalies of the development of the urinary system for the simultaneous study of the anatomical and topographical state and functional capacity of the abnormally developed kidney.